UHPLC-ESI-Orbitrap-MS analysis of biologically active extracts from Gynura procumbens (Lour.) Merr. and Cleome gynandra L. leaves - Chandradevan, Machap; Simoh, Sanimah; Mediani, Ahmed; Ismail, Nor Hadiani; Ismail, Intan Safinar; Abas, Faridah (2020)
This study aimed to determine the total phenolic content, DPPH scavenging, α-glucosidase, and nitric oxide (NO) inhibition of Gynura procumbens and Cleome gynandra extracts obtained with five different ethanolic concentrations. The findings showed that the 100% ethanolic extract of G. procumbens had the highest phenolic content and the lowest IC50 values for DPPH scavenging and NO inhibition activity compared to the properties of the other extracts. For C. gynandra, the 20% and 100% ethanolic extracts had comparably high total phenolic contents, and the latter possessed the lowest IC50 value in the NO inhibition assay. In addition, the 20% ethanolic extract of C. gynandra had the lowest IC50 value in the DPPH scavenging assay. However, none of the extracts from either herb had the ability to inhibit α-glucosidase enzyme. Pearson correlation analysis indicated a strong relationship between the phenolic content and DPPH scavenging activity in both herb extracts. A moderately strong relationship was also observed between the phenolic content and NO inhibition in G. procumbens extracts and not in C. gynandra extracts. The UHPLC-ESI-Orbitrap-MS revealed major phenolics from the groups of hydroxycinnamic acids, hydroxybenzoic acids, and flavonoid derivatives from both herbs, which could be the key contributors to their bioactivities. Among the identified metabolites, 24 metabolites were tentatively assigned for the first time from both species of studied herbs. These two herbs could be recommended as prospective natural products with valuable medicinal properties.